2012
DOI: 10.1002/cssc.201200738
|View full text |Cite
|
Sign up to set email alerts
|

Harmonising Production, Properties and Environmental Consequences of Liquid Transport Fuels from Biomass—2,5‐Dimethylfuran as a Case Study

Abstract: The rapid development in methods for transforming non-edible biomass into platform chemicals and fuels has accelerated over recent years. However, the determination of whether these 'next-generation' biofuels perform in a satisfactory manner in engines, turbines and burners has lagged behind. The evaluation of the ecological and toxicological aspects has also been unable to keep up. We show, by using 2,5-dimethylfuran (DMF) as a concrete example, how a range of studies is needed to establish the benefits and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Indeed, DMF has been recognized as a promising fuel additive because of its higher energy density as compared to ethanol (40 % greater), high octane number, and very low solubility in water. The flexibility of the process definitely reinforces its attractiveness for industrial implementation 8…”
Section: Methodsmentioning
confidence: 97%
“…Indeed, DMF has been recognized as a promising fuel additive because of its higher energy density as compared to ethanol (40 % greater), high octane number, and very low solubility in water. The flexibility of the process definitely reinforces its attractiveness for industrial implementation 8…”
Section: Methodsmentioning
confidence: 97%
“…With a resurgent interest in the synthesis of platform chemicals and biofuels from nonedible biomass and since the properties and gas‐phase pyrolytic/oxidation chemistries of furans have been the subject of much recent work , we have undertaken a study of this compound.…”
Section: Introductionmentioning
confidence: 99%
“…As a chemical that can be produced from biomass, 2,5-dimethylfuran (DMF) is suitable as a biofuel, with properties similar to those of gasoline (Roman-Leshkov et al, 2007;Simmie and Wurmel, 2013). Early studies on the thermal decomposition of furan series biofuels were reported by Grela et al (1985) and Lifshitz et al (1986Lifshitz et al ( , 1997Lifshitz et al ( , 1998.…”
Section: Introductionmentioning
confidence: 98%